Pengaruh Capital Structure dan Sales Growth terhadap Firm Value : pada Perusahaan Sektor Industrial yang Terdaftar di BEI Periode 2015-2024 - Sri Handayani; Mukhzarudfa, Mukhzarudfa; Ratih Kusumastuti (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the effect of capital structure and sales growth on firm value in industrial sector companies listed on the Indonesia Stock Exchange during the 2015–2024 period. This research uses a quantitative approach with secondary data obtained from company financial statements through the official website of the Indonesia Stock Exchange. The research sample consisted of 14 companies with a total of 140 observations selected using the purposive sampling method. The data analysis technique used was multiple linear regression analysis with the assistance of IBM SPSS version 31. The results showed that simultaneously capital structure and sales growth had a significant effect on firm value. Partially, capital structure had a positive and significant effect on firm value, indicating that a well-managed capital structure can increase company value. Meanwhile, sales growth did not have a significant effect on firm value. These findings indicate that investors tend to consider capital structure more than sales growth in assessing the value of companies in the industrial sector.